Avian Influenza H5N1 in Naturally Infected Domestic Cat - Songserm, Thaweesak (Centers for Disease Control and Prevention, 2006)
We report H5N1 virus infection in a domestic cat infected by eating a pigeon carcass. The virus isolated from the pigeon and the cat showed the same cluster as the viruses obtained during the outbreak in Thailand. Since cats are common house pets, concern regarding disease transmission to humans exists.